2015
DOI: 10.21500/20112084.650
|View full text |Cite
|
Sign up to set email alerts
|

Examining materialistic values of university students in thailand

Abstract: The purposes of this study were to classify university students in terms of their materialism and to compare the difference in certain attributes among the segments. Student attributes taken into consideration included father's educational level and occupation, money received from family, family communication and susceptibility to peer influence. In this survey research, questionnaires were used to collect data from 620 students ranging from 18 to 21 years old in Bangkok. Cluster analysis was used where studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
(42 reference statements)
0
3
0
2
Order By: Relevance
“…In recent decades researchers have increasingly focused on youths' values. Substantial and / or dynamic parameters of personal value-meaning systems of youths in connection to social, economic, politic, cultural factors were investigated worldwide (Karvonen et al, 2012;Lan, 2009;Likitapiwat et al, 2015;Maercker et al, 2015;Meral, 2000;Petrov, 2008;Salikhova, 2015a).…”
Section: Youths' Valuesmentioning
confidence: 99%
“…In recent decades researchers have increasingly focused on youths' values. Substantial and / or dynamic parameters of personal value-meaning systems of youths in connection to social, economic, politic, cultural factors were investigated worldwide (Karvonen et al, 2012;Lan, 2009;Likitapiwat et al, 2015;Maercker et al, 2015;Meral, 2000;Petrov, 2008;Salikhova, 2015a).…”
Section: Youths' Valuesmentioning
confidence: 99%
“…Money as a material aspect becomes a form of expression for young persons, and also reveals an attitude toward possessions that are seen through the prism of happiness, which become the center of their lives. Likitapiwat [72] observed that the family environment is important in the development of material values and that parental attitudes toward child-raising and behavior when their needs are not being met become a cause of material values. Parents also use material things to shape the behavior of their children [73].…”
Section: Discussionmentioning
confidence: 99%
“…Al respecto, según Banerjee y Ditmar (2008), los jóvenes que muestran altos niveles de preocupación por las opiniones que los demás tienen de ellos son más propensos a tener deudas en el futuro, especialmente si su grupo de referencia pertenece a un nivel socioeconómico o de ingresos superior (Gentina 2014;Hoeve et al, 2014). Este complejo sistema de relaciones entre los adolescentes y sus grupos de referencia puede generar incertidumbre y ansiedad al rechazo, de modo que el consumo funciona como regulador emocional en la búsqueda de integración (Isaksen & Roper, 2012;Jiang et al, 2015;Likitapiwat et al, 2015).…”
Section: Discussionunclassified
“…Al respecto, se aprecia que adolescentes con altos valores materiales se preocupan más por la comparación social, son más susceptibles a la influencia normativa de sus pares, prestan mucha atención a la aprobación o desaprobación de sus compras (Kasser et al, 2007) y comparan más sus posesiones con las de sus amigos (Likitapiwat et al, 2015).…”
Section: Susceptibilidad Al Efecto De Paresunclassified